…Exhaust all sources for this subject first – Jan Matejko - Kłak-Ambrożkiewicz, Marta (In the Mirror of Things, 2022)
The biography of things, in the biography of the painter, in the biography of the work, in the biography of the house that became a museum. History recreated on the basis of sources – receipts, inventories, photographs, correspondence in accordance with the artist’s motto. Jan Matejko (1838–1893) is the author of more than three hundred twenty oil paintings, several thousand drawing sketches, a couple of hundred projects of the polychrome, stained glass, altars and statues. He was a titan, not only artistic. His paintings received the highest awards. Also, honorary memberships of the European artistic associations were bestowed on him. In 1873 Matejko took the management of Cracow Fine Arts School. Matejko the collector – artist, treated very often these monumental objects as the painting requisites not only in his own artistic emprises but also in the works of students of The Krakow Academy of Art, which was headed by him in 1873–1893. The intention of Jan Matejko was the presentation of the collector’s set for broad audience. Currently this idea is being realized as the permanent museum exposition and temporary exhibitions.